Determination of lactate dehydrogenase (LDH) and Bcr-Abl transcript in the follow-up of patients with chronic myeloid leukemia - doi: 10.4025/actascihealthsci.v32i2.6408 - Tatakihara, Roberto Iemirsu; Amarante, Marla Karine; Aoki, Mateus Nóbrega; Oda, Julie Massayo Maeda; Fujita, Thiago Cezar; Watanabe, Maria Angelica Ehara (Acta Scientiarum. Health Sciences, 2010)
Chronic myeloid leukemia (CML) is a malignant myeloproliferative disorder that originates from a pluripotent stem cell characterized by abnormal release of the expanded, malignant stem cell clone from the bone marrow into the bloodstream. The vast majority of patients with CML present Bcr-Abl transcripts. Lactate dehydrogenase (LDH) is considered a biochemical marker common for tumor growth, anaerobic glycolysis and has been considered a poor prognostic factor for acute myeloid leukemia. Therefore, this study aimed to evaluate the concentration of LDH in plasma and the detection of the Bcr-Abl transcripts in patients with CML and healthy donors. We analyzed 22 patients demonstrably diagnosed with CML and 56 healthy donors. LDH concentration in plasma was higher in patients with CML. All patients with CML in this study were under treatment, but even so four patients had the Bcr-Abl (b3a2) transcript in peripheral blood. Two out of the four patients with b3a2 showed higher LDH (486 U L-1 and 589 U L-1). Thus, although the study was conducted with small numbers of samples, it is possible to suggest therapy alteration for two patients who presented transcript b3a2 in the peripheral blood samples and whose LDH concentration was high, in order to improve the disease.